Sub-erythemal ultraviolet radiation reduces metabolic dysfunction in already overweight mice. Issue 1 (April 2017) - Fleury, Naomi; Feelisch, Martin; Hart, Prue H; Weller, Richard B; Smoothy, Jordan; Matthews, Vance B; Gorman, Shelley
Abstract : Exposure to sunlight may limit cardiometabolic risk. In our previous studies, regular exposure to sub-erythemal (non-burning) ultraviolet radiation (UVR) reduced signs of adiposity and cardiometabolic dysfunction in mice fed a high-fat diet. Some of the observed effects were dependent on skin release of nitric oxide after UVR exposure. Here, we examine the effects of sub-erythemal UVR on signs of adiposity and metabolic dysfunction in already overweight mice, comparing the effects of two sunlamps with distinct emitted light spectra. Mice were fed a high-fat diet from 8 weeks of age, with UVR administered twice a week from 14 weeks of age until they were killed at 20 weeks of age. Mice were irradiated with the same dose of UVB radiation (1 kJ/m 2 ) from either FS40 (65% UVB, 35% UVA) or CLEO (4% UVB, 96% UVA) sunlamps, but substantially more UVA from the latter. FS40 UVR (but not CLEO UVR) significantly reduced mouse weights and weight gain, compared to mice fed a high-fat diet (only). These effects were dependent on nitric oxide. Conversely, CLEO UVR (but not FS40 UVR) significantly reduced circulating LDL cholesterol. Both light sources reduced fasting insulin levels, and the extent of hepatic steatosis; the latter was reversed by topical application of cPTIO, suggesting an important role for skin release of nitric oxide in preventing hepatic lipid accumulation. These results suggest that there may be a number of benefits achieved by regular exposure to safe (non-burning) levels of sunlight or UV-containing phototherapy, with effects potentially dependent on the predominance of the wavelengths of UVR administered.